Does skull morphology constrain bone ornamentation? A morphometric analysis in the Crocodylia. Issue 2 (7th April 2016) - Clarac, F.; Souter, T.; Cubo, J.; de Buffrénil, V.; Brochu, C.; Cornette, R.
Abstract: Previous quantitative assessments of the crocodylians' dermal bone ornamentation (this ornamentation consists of pits and ridges) has shown that bone sculpture results in a gain in area that differs between anatomical regions: it tends to be higher on the skull table than on the snout. Therefore, a comparative phylogenetic analysis within 17 adult crocodylian specimens representative of the morphological diversity of the 24 extant species has been performed, in order to test if the gain in area due to ornamentation depends on the skull morphology, i.e. shape and size. Quantitative assessment of skull size and shape through geometric morphometrics, and of skull ornamentation through surface analyses, produced a dataset that was analyzed using phylogenetic least‐squares regression. The analyses reveal that none of the variables that quantify ornamentation, be they on the snout or the skull table, is correlated with the size of the specimens. Conversely, there is more disparity in the relationships between skull conformations (longirostrine vs. brevirostrine) and ornamentation. Indeed, both parameters GApit (i.e. pit depth and shape) and OArelat (i.e. relative area of the pit set) are negatively correlated with snout elongation, whereas none of the values quantifying ornamentation on the skull table is correlated with skull conformation. It can be concluded that bone sculpture on the snout is influenced by different developmental constrains than on the skull table and is sensible to differences in the local growth 'context' (allometric processes) prevailing in distinct skull parts. Whatever the functional role of bone ornamentation on the skull, if any, it seems to be restricted to some anatomical regions at least for the longirostrine forms that tend to lose ornamentation on the snout.